Identifying Characteristic of Power Quality Problems on Solar Electric Power Generation - Dani Ali, Nurhalim; Azhari Zakri, Azriyenni (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2018)
The influence of connected electrical load will cause significant problems on Solar Electric Power Generator (SEPG). The problems are extremely important to be identification in order to provide electrical energy optimally. The objective of this paper is tantamount to investigate the impact of household electrical load on SEPG with variation and continuous electrical load. The identification of power quality was made by marking several test point on each output of SEPG unit. The level quality of voltage and frequency system needed to be measured and observed its performance indicator level. Furthermore, it compared by existing standard. To variation electrical load test, the results showed that the frequency of the system changed from 52 Hz to 262 Hz. In other hands, the frequency rose about five times against normal frequency. The continuous load test, that frequency of system fluctuated around 52 Hz to 156 Hz that also showed abnormal operation of SEPG.